Biomarkers-in-cardiology 8 RE-VISITED: consistent safety of early discharge with a dual marker strategy combining a normal hs-cTnT with a normal copeptin in low-to-intermediate risk patients with suspected acute coronary syndrome : a secondary analysis of the randomized biomarkers-in-cardiology 8 trial - Giannitsis, Evangelos; Garfias-Veitl, Tania; Slagman, Anna; Searle, Julia; Müller, Christian; Blankenberg, Stefan; Haehling, Stephan von; Katus, Hugo; Hamm, Christian; Huber, Kurt; Vollert, Jörn O.; Möckel, Martin (Cells, 2022)
Regarding the management of suspected Non-ST-segment-elevation acute coronary syndrome (ACS), the main Biomarker-in-Cardiology (BIC)-8 randomized controlled trial study had reported non-inferiority for the incidence of major adverse cardiac events at 30 days in the Copeptin group (dual marker strategy of copeptin and hs-cTnT at presentation) compared to the standard process (serial hs-cTnT testing). However, in 349 (38.7%) of the 902 patients, high-sensitivity cardiac troponin was not available for the treating physicians. High sensitivity cardiac troponin T was re-measured from thawed blood samples collected at baseline. This cohort qualified for a re-analysis of the 30-day incidence rate of MACE (death, survived cardiac death, acute myocardial infarction, re-hospitalization for acute coronary syndrome, acute unplanned percutaneous coronary intervention, coronary bypass grafting, or documented life-threatening arrhythmias), or components of the primary endpoint including death or death/MI. After re-measurement of troponin and exclusion of 9 patients with insufficient blood sample volume, 893 patients qualified for re-analysis. A total of 57 cases were detected with high sensitivity cardiac troponin T ≥ 14 ng/L who had been classified as “troponin negative” based on a conventional cardiac troponin T or I < 99th percentile upper limit of normal. Major adverse cardiac events rates after exclusion were non-inferior in the Copeptin group compared to the standard group (4.34% (95% confidence intervals 2.60-6.78%) vs. 4.27% (2.55-6.66%)). Rates were 53% lower in the per-protocol analysis (HR 0.47, 95% CI: 0.18-1.15, p = 0.09). No deaths occurred within 30 days in the discharged low risk patients of the Copeptin group. Copeptin combined with high sensitivity cardiac troponin is useful for risk stratification and allows early discharge of low-to-intermediate risk patients with suspected acute coronary syndrome is as safe as a re-testing strategy at 3 h or later.
Gesehen am 29.11.2022